2011
DOI: 10.7863/jum.2011.30.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Tall Cell Variant of Papillary Thyroid Carcinoma

Abstract: apillary thyroid carcinoma, the most common form of thyroid carcinoma (85% of cases), is well known for its indolent clinical behavior with a high survival rate compared to those of other malignancies. When papillary thyroid carcinoma with frequent recurrences and distant metastasis with aggressive clinical behavior is encountered, it has been pathologically diagnosed as a variant. 1-3 Among the variants of papillary thyroid carcinoma, the tall cell variant frequently has lymph node metastasis, distant metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Accurate preoperative diagnosis has been difficult to secure. Choi et al [15] studied in a retrospective fashion the clinical and sonographic features of eight patients with 10 TCV tumors. The inclusion criteria for a diagnosis of TCV included a tumor 'composed of more than 50% tall cells, a tall cell height at least twice its width, eosinophilic tall cell cytoplasm, and nuclear features characteristic of papillary thyroid carcinoma such as nuclear irregularities, clearing and overlapping, grooves, and pseudoinclusions'.…”
Section: Preoperative Diagnosismentioning
confidence: 99%
“…Accurate preoperative diagnosis has been difficult to secure. Choi et al [15] studied in a retrospective fashion the clinical and sonographic features of eight patients with 10 TCV tumors. The inclusion criteria for a diagnosis of TCV included a tumor 'composed of more than 50% tall cells, a tall cell height at least twice its width, eosinophilic tall cell cytoplasm, and nuclear features characteristic of papillary thyroid carcinoma such as nuclear irregularities, clearing and overlapping, grooves, and pseudoinclusions'.…”
Section: Preoperative Diagnosismentioning
confidence: 99%
“…Due to the rarity of TCV, only one study [23] reported the distinctive sonographic appearance of this variant to date. In that study, Choi et al reviewed the sonographic features of 10 TCV and found that TCV always associated with microlobulated, markedly hypoechoic solid nodules, extrathyroidal extension and lymph node metastasis.…”
Section: Pre-operative Diagnosismentioning
confidence: 99%
“…Classic TCV tumors are “composed of more than 50% tall cells, a tall cell height at least twice as long as its width, eosinophilic tall cell cytoplasm, and nuclear features characteristic of PTC such as nuclear irregularities, clearing and overlapping, grooves, and pseudoinclusions” [29]. Preoperative sonographic findings indicative of TCV often overlap significantly with those indicative of cPTC, but TCV often harbors features that are more aggressive, such as hypoechogenicity, evidence of ETE, microcalcifications, and macrocalcifications.…”
Section: Discussionmentioning
confidence: 99%